PENGARUH PENGEMBANGAN KREATIVITAS, MOTIVASI BERUSAHA DAN KONDISI LINGKUNGAN TERHADAP PENINGKATKAN PENGHASILAN ALUMNI PESERTA PROGRAM PENDIDIKAN KECAKAPAN HIDUP DI LEMBAGA KURSUS DAN PELATIHAN (LKP) DINAS PENDIDIKAN, PEMUDA DAN OLAHRAGA PROVINSI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2011 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The Influence of Creativity Development, Effort Motivation and Environmental Condition to the Increase in income of PKH Program Participant Alumni Held by Yogyakarta Special Region Education, Youth and Sport Office 2011. Thesis. Yogyakarta: Postgraduate Program, Education Management Study Program, Yogyakarta Taman Siswa University, 2013. The research is aimed at studying the influence of creativity development, effort motivation and environmental condition to the increase in income of PKH participants alumni held by Yogyakarta Special Region Education, Youth and Sport Office 2011. This was a influence study employing a quantitative approach, with 510 populations of PKH participant alumni, spread to 25 institutions as the block-grant beneficence of the Yogyakarta Special Region Education, Youth and Sport Office 2011. The research covered 163 alumni samples spread to 15 institutions for the research feasibility based on Harry King nomogram calculation with 5% error while 208 failed to reach, using Proportionate Random Sampling technique and questionnaire data collection. The questionnaire was tested on 30 respondents out of the samples through the validity and reliability tests. Data analysis utilized double correlation and partial correlation techniques, with SPSS version 16 data processor. The descriptive analysis reveals that variables of creativity development, effort motivation and environmental condition to the increase in income of PKH participant alumni held by Yogyakarta Special Region Education, Youth and Sport Office 2011 indicate 0.559 so then moderate category, proven by the score between 0.40 – 0.599. Thus, the study shows the positive and significant simultaneous effect among creativity development, effort motivation and environmental condition to the increase in income of PKH participants alumni held by Yogyakarta Special Region Education, Youth and Sport Office 2011. Meanwhile, the variable of creativity development is the dominant factor, for it has the greatest effective and relative contribution among the other variables. Effective contribution sequentially from the greatest is creativity development based on the participant basic skills, environmental condition and effort motivation.